A Study On Cultural Factors Affecting Team Effectiveness Among Multi-Cultural Teams In The Context Of Knowledge Management - Malani, Achro (2002)

(untitled)
In view of the escalating interests in the study of diverse workforce, this study is undertaken to explore the effect of cultural factors on team effectiveness in the context of knowledge management. This study looks at the knowledge sharing aspect of knowledge management. The role of the organization as a moderator between the two factors and in encouraging knowledge sharing is also examined. The objective of this research was to study the cultural factors that positively contributed towards team effectiveness and assisted in the process of knowledge sharing among team members. It also examined the cultural factors that inhibited the progress of these teams and hinders the process of knowledge sharing among team members. The sample chosen for this study comprised of middle management personnel representing the three major races; Malays, Chinese and Indians from three American multi-national companies located in Northern Kedah and Perlis. The findings confirmed that cultural factors do contribute towards team effectiveness and assisted in the process of knowledge sharing. The findings concurred that there was a positive correlation between Islamic work ethics and team effectiveness. The relationship between ingroup/outgroup interpersonal relationship, power distance and 'gotong-royong and budi' values and team effectiveness were partially supported. No significant relationship was found between collectivism, self vs collective interests, concern for face and team effectiveness. However the role of the organization significantly moderated the relationship in Islamic work ethics, 'gotong-royong and budi' values, and ingroup/outgroup interpersonal relationship and team effectiveness and contributed towards knowledge sharing. Organizational role significantly moderated the relationship between Concern for face and team effectiveness although this relationship was found to hinder knowledge sharing among team members. The relationship between collectivism, self vs collective interests were partially supported. It was observed that management had to play lead role in cultivating these traits so that members willingly give up their personal interests over collective interests and share their knowledge without feeling threatened. The relationship between power distance and team effectiveness were found to be not significant and this is important as it will not hinder knowledge sharing. This study was significant as it shows the impact of cultural factors on team effectiveness in the context of knowledge sharing. Another important finding was the significant relationship between 'gotong-royong and budi' values, Islamic work ethics and team effectiveness and its positive contribution towards knowledge sharing. These factors need to be further explored, as they will provide valuable insight into the work behavior patterns of the Malaysian workforce particularly in the context of knowledge management.